Effect of composted sewage sludge amendment on soil nitrogen and phosphorus availability - Coutinho, João (2011)
Municipal sewage sludge previously composted with sawdust (CSS) was applied to an eutric sandy cambisol at rates of 7.5, 15.0, 22.5, and 30 g·kg-1. Incubation and pot experiments were conducted to evaluate CSS effectiveness on nitrogen (N) and phosphorus (P) soil availability and on plant nutrition. The CSS rates did not increase soil mineral N and had little effect on organic P and on labile forms of P. Efficiency of total applied P was 17% for the soil labile forms and 4.8% for the resin extractable fraction. In contrast, CSS significantly increased hydroxide extractable inorganic P and nonextractable soil P fraction. The major portion of the increment on nonextractable forms was at the expense of HC1 extractable P fraction [calcium (Ca)-bounded], dominant on the original CSS. Thus, chemical rather than biological reactions lead to the redistribution of CSS-borne P to more firmly held forms after its application to the soil. Ryegrass dry matter yield, N content, and N uptake did not increase in CSS-treated soils. Plant P content increased at the second harvest, but the effect was nil in the subsequent harvest. Total P uptake increased from 14.1 to 20.2 mg·pot-1, but percentage P recovery by ryegrass was modest, averaging 2.5% of the CSS-borne P. Results suggest that moderate application of CSS to agricultural systems are inadequate for crop growth but may contribute to nutrient recycling without environmental risks related to N and P loss.